2022
DOI: 10.3389/fgene.2021.705512
|View full text |Cite
|
Sign up to set email alerts
|

INHBA is a Prognostic Biomarker and Correlated With Immune Cell Infiltration in Cervical Cancer

Abstract: Background: Inhibin A (INHBA), a member of the TGF-β superfamily, has been shown to be differentially expressed in various cancer types and is associated with prognosis. However, its role in cervical cancer remains unclear.Methods: We aimed to demonstrate the relationship between INHBA expression and pan-cancer using The Cancer Genome Atlas (TCGA) database. Next, we validated INHBA expression in cervical cancer using the Gene Expression Omnibus (GEO) database, including GSE7803, GSE63514, and GSE9750 datasets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Previous studies have shown that mRNA may affect the proliferation of cervical cancer cells through immune in ltrating cells [33]. Zhao et al demonstrated that the INHBA gene is a prognostic biomarker and correlated with immune cell in ltration in cervical cancer [34]. In our study, neutrophils were positively correlated with the EREG gene and the HOPX gene, but negatively correlated with the SYNGR3 gene, which is consistent with our previous analysis of prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that mRNA may affect the proliferation of cervical cancer cells through immune in ltrating cells [33]. Zhao et al demonstrated that the INHBA gene is a prognostic biomarker and correlated with immune cell in ltration in cervical cancer [34]. In our study, neutrophils were positively correlated with the EREG gene and the HOPX gene, but negatively correlated with the SYNGR3 gene, which is consistent with our previous analysis of prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Differential expression between the three clusters (Figure 3C) identified high expression of TUBA1B in cluster 5, which is associated with poor prognosis in NSCLC, suggesting persisting drug tolerance after the holiday period. Similarly, we observe differential expression of INHBA in cluster 3, a senescence mediator that’s associated with prognosis in many cancer types (Zhao et al, 2022). Interestingly, TUBA1B and INHBA expression are significantly reduced in the day 19 population that was not retreated with Erlotinib.…”
Section: Resultssupporting
confidence: 53%
“…GSE9750, an mRNA microarray, was used to identify key CC genes [ 46–48 ]. In previous studies, researchers used more than three microarrays from the GEO database, including GSE9750, to screen key genes in CC [ 47–49 ]. When performing different bioinformatic strategies in our study, we only used GSE9750, along with metascape for GO enrichment, and the TCGA database to identify that DCN was the key gene in CC; this result was different from those of previous studies.…”
Section: Discussionmentioning
confidence: 99%